USE OF INTRANASAL ESKETAMINE IN THE TREATMENT OF TREATMENT-RESISTANT DEPRESSION: A CASE REPORT - Jerotić, Stefan; Poleksić, Joko; Ivković, Maja; Latas, Milan (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Treatment-resistant depression (TRD) refers to a depressive episode that has not responded to treatment with two antidepressants. Pharmacological strategies for treating TRD involve a complex process, which includes several options for the use of different psychopharmaceuticals, fundamentally consisting of: (1) substituting/optimizing the dose of antidepressants, or (2) augmenting antidepressant therapy. Within the augmentation strategy, NMDA antagonists, including intranasal esketamine, play a significant role. Current research suggests that the application of intranasal esketamine as an augmentation agent is an effective pharmacological strategy in the treatment of TRD. Case report: In this paper, we present the successful application of intranasal esketamine in co-administration with a serotonin/norepinephrine reuptake inhibitor (SNRI antidepressant) in a patient with TRD. Conclusion: Further research is necessary to better understand the mechanisms of action, dosing modalities, as well as the long-term outcomes and safety profile of this approach.
Keywords: depression; treatment-resistant depression; pharmacological treatment; intranasal esketamine